Ethanol inhibits cooling-induced spinal seizures (Gaceta de Ciencias Veterinarias, 2019)
The isolated spinal cord can generate Paroxysmal seizure-like activity similar to those observed in intact animals. Patterns of tonic-clonic seizures can be induced by sudden cooling the isolated spinal cord-hindleg preparation, an experimental model of seizures that depends on release of excitatory amino acids (EAA). We examine whether clinically relevant doses of ethanol can prevent the onset and severity of spinal seizures. The characteristic phases of seizures and their intensity were assessed by recording muscle contractions. The onset and duration of seizures were measured after intralymphatic (i.l.) administration of ethanol at doses of 1.5, 2.5 and 5 g/kg diluted to 10% with Ringer’s solution. The tonic phase of seizures was effectively shortened or eliminated in a dose dependent manner when ethanol was given at 1.5 and 2.5 g/kg. At doses of 5 g/kg ethanol abolished all phases of seizures while producing moderated motor impairment. The latency of seizure onset was enhanced by 71% and 145% at ethanol doses of 1.5 and 2.5 g/kg, respectively. The effect of ethanol on the pattern of seizure activity was compared with that of known antagonists of EAA receptors. We concluded that ethanol inhibition of the tonic phase was linked to inhibition of N-methyl-D-aspartate (NMDA) receptors, while depression of the clonic phase of seizure was due to its blocking action on α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate(AMPA) receptors; on the other hand, its effect on the latency of seizure onset resembled that of drugs acting by enhancing γ-amino-butyric acid(GABAA) receptor activity.
Keywords: Alcohol; spinal cord; seizures; cooling; excitatory amino acids